Kring några nyfunna Geijermanuskript - af Geijerstam, Claes (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1984)
E. G. Geijer’s instrumental music - II new find A new find of piano and chamber music by Eric Gustaf Geijer (1783-1847) is presented. Geijer is one of the central figures in Swedish music during the transitory period between classicism and rorniinticism. despite the fact that composition was but ii diversion from his activities as professor of history at the University of Uppsala. He was largely an autodidact as composer but by diligent practice - he was ii skilled pianist - he acquired good knowledge of contemporary trends in music. in addition to a number of already known compositions. the find of notes comprises two compositions that have earlier been known only in more or less unfinished form. One is ii sonata tor cello and piano composed in 1826. ol’ which the first movement now can be reconstructed in its entirety. and the other ii trio for violin. cello and piano, of which only ii fragment of the piano part was known earlier. The trio is particularly interesting as, in the contemporary Swedish context. it is an unusually ambitious composition in variations. The compositions that have now been found are all handwritten copies which belonged to Geijer’s friend since chiIdhood. Christ i ii ii af Geijerstam. who was the author’s great-great-great grand mot her on the paternal side.